2012
DOI: 10.5424/sjar/2012103-362-11
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced resistance to Rhizoctonia solani by combined expression of chitinase and Ribosome Inactivating Protein in transgenic potatoes (Solanum tuberosum L.)

Abstract: Potato (Solanum tuberosum L.) is susceptible to many fungal pathogens including Rhizoctonia solani. In the present study, the potato cultivar Desirée was transformed via Agrobacterium tumefaciens strain GV3101 containing the binary plasmid pGJ132 harboring both the chitinase (chiA) and rip30 genes. The potato leaf disc was used as an explant for transformation. PCR, Southern blot and Western blot were used for characterization of the transgenic plants. In this study it was shown that not all the plants develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…To enhance the antifungal activity of RIPs, genes encoding chitinases have also been introduced [79,84,86,99,110,111], which as we have seen exert a synergistic effect with…”
Section: Transgenic Plants Resistant To Fungal Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the antifungal activity of RIPs, genes encoding chitinases have also been introduced [79,84,86,99,110,111], which as we have seen exert a synergistic effect with…”
Section: Transgenic Plants Resistant To Fungal Infectionmentioning
confidence: 99%
“…To enhance the antifungal activity of RIPs, genes encoding chitinases have also been introduced [ 79 , 84 , 86 , 99 , 110 , 111 ], which as we have seen exert a synergistic effect with RIPs, and even the lectin WGA [ 99 ] ( Figure 2 ). In addition, some transgenic plants carrying RIPs are also resistant to viruses and insects [ 9 , 12 ], which adds even more interest to this type of strategy.…”
Section: Transgenic Plants Resistant To Fungal Infectionmentioning
confidence: 99%
“…Transformed Indian mustard ( Brassica juncea ) expressing both barley RIP and chitinase showed 44% reduction in Alternaria brassicae hyphal growth in an in vitro assay and transgenic plants sprayed with an A. brassicae spore suspension showed reduced numbers, sizes, and expansion of lesions compared to wild type plants [ 133 ]. Similarly, potato plants overexpressing a combination of RIP and chitinase showed enhanced resistance to Rhizoctonia solani in a greenhouse assay [ 134 ]. Chopra and Saini [ 135 ] reported that transformed blackgram ( Vigna mungo ) plants expressing the same set of genes arrested the growth of Corynespora cassiicola in an in vitro antifungal assay and the plants also showed less disease symptoms compared to wild type plants after being sprayed with a spore suspension.…”
Section: Physiological Roles Of Cereal Ripsmentioning
confidence: 99%